O impacto da pandemia pelo Covid-19 na prática de atividade física de escolares - Silva, Wesley Pereira da (Universidade Federal do Tocantins, 2024)
This work aims to conduct an integrative review of the literature on the impact on physical activity of schoolchildren aged 9 to 16 years old. The study covers the entire national territory. What was the pandemic period like for this group of people in relation to physical activity, especially Physical Education classes? The research on this topic was carried out in the search engines Research Rabbit and Open Knowledge where the terms “Schools”, “Physical Activity”, “Covid-19” were used simultaneously. The same search was carried out in both search engines, and with the delimitations on what the integrative review would be like, a partial reading, exclusion and then a complete reading of the 5 articles that covered the topic sought were carried out. The period sought was from 2020, the year in which the pandemic actually began in Brazil, until 2023, the year in which we still have impacts from the pandemic. It is concluded that these impacts greatly disrupted this group of people, in all aspects: in the health, intellectual and social areas. We propose a physical activity notebook that can be used safely, as it is an easy-to-understand and easily applicable notebook that can be used anywhere, even with mobility restrictions.